Arctic Ozone Depletion Observed by UARS MLS during the 1994-95 Winter - Manney, G. L.; Froidevaux, L.; Waters, J. W.; Santee, M. L.; Read, W. G.; Flower, D. A.; Jarnot, R. F.; Zurek, R. W. (2004)
The Arctic lower stratosphere was unusually cold and the polar vortex